Hubungan Ketahanan Pangan, Pola Asuh, dan Tingkat Kecukupan Gizi dengan Kejadian Stunting Balita 6-59 Bulan di Puskesmas Dawe, Kabupaten Kudus: The Association of Food Security, Parenting Patterns, and Nutritional Adequacy Levels with Stunting among Toddlers Aged 6–59 Months at the Dawe Community Health Center, Kudus - Rahmatika, Tarisca; Pangestuti, Dina Rahayuning; Asna, Alfi Fairuz (Amerta Nutrition, 2024)
Background: Stunting is a significant issue in Kudus District, with a 2023 prevalence of 15.7%, driven by factors like parenting patterns, food security, and nutritional intake. Despite being food-secure, the Dawe Health Center area has the third-highest stunting rate in Kudus Regency. Objectives: Examine the correlations of family food security, nutritional adequacy levels, and parenting patterns with the incidence of stunting among toddlers at the Dawe Community Health Center. Methods: This cross-sectional study sampled 86 mother-toddler pairs at the Dawe Community Health Center purposively. Data on stunting in toddlers and maternal height were assessed using anthropometric measurements. Information on general characteristics, parenting patterns, and household food security was gathered with interviews, questionnaires, and observations. Nutritional intake data were collected with 2×24-hour recall and the SQ-FFQ. Associations were analyzed using the chi-square test, Fisher's exact test, and multiple logistic regression analysis. Results: The study found that respondents had good parenting patterns (58.1%) and were food-secure (74.4%). Energy (73.3%), zinc (91.9%), calcium (57%), iron (54.7%), and vitamin D (38.4%) intake were sufficient. In addition, all toddlers had sufficient protein and vitamin A. Bivariate test results showed that parenting patterns (p-value = 0.004), food security (p-value=0.006), energy adequacy (p-value<0.001), and calcium adequacy (p-value<0.001) were correlated with stunting. Multivariate test showed that energy adequacy (OR=7.7; p-value=0.003), calcium adequacy (OR=5.2; p-value=0.007), and parenting patterns (OR=5.3; p-value=0.006) were dominant factors associated with stunting. Conclusions: The dominant factors influencing the occurence of stunting among toddlers at the Dawe Community Health Center were the levels of nutritional adequacy (energy, calcium) and parenting patterns.